Public Health and Social Reforms in Portugal (1780-1805) - Abreu, Laurinda (2017)
Public health and social reforms in Portugal (1780–1805) presents an innovative analysis of a unique period for social and public health policy in Portuguese history. With a firm basis in archival research, the book examines a lesser-known facet of one of the most fascinating and controversial figures in the late Ancien Regime in Portugal: Diogo Inácio de Pina Manique, the Intendant-General of Police from 1780 to 1805. By combining the resources of the Intendancy with those of the Casa Pia, an institution for welfare provision and social control that he set up just a month after being appointed, Pina Manique attempted to introduce a variety of projects designed to create a prosperous, healthy, well-educated, informed, clean and hard-working country less inclined to vice and immorality, in which the people would be obedient and the upper classes more magnanimous. One of his greatest achievements was perhaps to understand the link between ill health and poverty and therefore to regard public health as a key area of governance.